Samoloty mysliwskie : skrzydlo samolotow bojowych wizyta z przewodnikiem - Clancy, Tom, 1947-2013.; Luba, Piotr (Gdansk : Gdanski Dom Wydawniczy, 1998)
Polish translation of"Fighter Wing". A guided tour of a United States Air Force combat wing.
Translation of: Fighter wing : a guided tour of an Air Force combat wing.
Keywords: United States. -- Air Force. -- Air Combat Command. -- Wing, 366th.; Fighter planes -- United States -- Design and construction; Airplanes, Military -- United States -- Armament